Archaic Oirat substratum of the “circa-Altai musical Kulturkreis” in Tuva - Todoriki, Masahiko (The New Research of Tuva, 2017)
Worldwide fame for Tuvan music is now immovable. The vocal phenomenon xöömei or Tuvan throat-singing, in particular, attracts music fans around the world. On the other hand, so called “overtone-singing” or “throat-singing,” the vocal sound of a fundamental drone with a flute-like melody of a series of chosen formants, also is reported sporadically in Tibet, Xhosa, Rajasthan, Sardinia, USA, the former Yugoslavia etc. It is still challenging to define whether specific features can be distinguishable unifying various “overtone-singing” from other vocalization. However, it was implied the music, including throat-singing, among peoples dwelling the Sayano-Altai region can be well coordinating as a single musical Kulturkreis. Here is an attempt to reconstruct recent history of the music of this zone, consulting historical records and linguistic materials from Tuva and surrounding regions.